OPTICAL COHERENCE TOMOGRAPHY OPPORTUNITIES IN DETECTION OF CORONARY PLAQUE MORPHOLOGY - I. A. Mustafina; N. Sh. Zagidullin; V. Sh. Ishmetov; V. N. Palvov (Креативная хирургия и онкология, 2017)
Optical coherence tomography (OCT) is a method of intravascular imaging of coronary arteries with a superior resolution, based on interferometry. The following review presents the technical features of OCT systems, basic characteristics of OCT images. There has been analyzed the experience in detection of vulnerable plaque, distinguishing plaque morphology as a mechanism of acute coronary syndrome. This review focuses on the applicability of OCT in research and clinical practice in the field of invasive cardiology.